JCAH accreditation and the hospital library: a guide for librarians. - Topper, J M (1980)
The continuing effort to develop standards for libraries in health care institutions has resulted in the creation of two broad groups of standards: (1) quantitative and specific, and (2) qualitative and flexible. The library standards of the Joint Commission on Accreditation of Hospitals (JCAH), a major example of the second type, were revised and expanded considerably in 1978, bringing them into line with standards for other hospital departments. Possible areas of unclarity or difficulty for the librarian in complying with the revised JCAH standards are discussed, including those relating to staffing, consultants, library technicians, analysis of resources, assessment of needs, documentation, policies and procedures manuals, and the library committee. The JCAH site visit, including preparation of the Hospital Survey Profile, gathering information for the surveyor, and the summary conference, offers opportunities to librarians to participate in an institution-wide effort, to upgrade management practices, and to demonstrate the need for, and effectiveness of, library services in their hospitals.